Heatwaves and Novel Host Consumption Increase Overwinter Mortality of an Imperiled Wetland Butterfly - Abarca, Mariana; Larsen, Elise A.; Ries, Leslie (Frontiers in Ecology and Evolution, 2019)
Disruptive effects of climate change include range shifts, phenological mismatches among consumers and producers, and population declines. While these biological alterations have been widely documented, studies identifying specific mechanisms linking climate change to population declines are scarce. Extreme events, such as heatwaves can have devastating effects on living organisms and are increasing in frequency as Earth warms. Hence, understanding the effects of heatwaves on insects is necessary to inform conservation efforts and to develop predictions of population dynamics under future climate scenarios. Here, we experimentally evaluated the effects of heatwaves on the survival and phenology of the Baltimore Checkerspot (Euphydryas phaeton phaeton), a wetland butterfly with imperiled populations that has incorporated a novel host. We performed laboratory manipulations (implementing realistic temperature regimes) to assess the effect of heatwaves during summer and winter on the survival and phenology of E. p. phaeton. In addition, we analyzed historical temperature records to quantify the incidence of heatwaves within E. p. phaeton’s range to assess their potential role in the decline of southeastern populations. We found that winter heatwaves with maximum temperatures of 20°C can have more devastating effects on survival than summer heatwaves (up to 41°C). Eggs endured acute heat stress during summer with no significant effects on phenology and survival; similarly, pre-overwintering larvae were robust to heatwave exposure, as only the most intense heatwave treatment reduced their survival (37% reduction compared to control conditions). By contrast, dormant larvae were the most vulnerable stage, as they lost from 2 to 6% of their body mass after a three-day summer heatwave. Furthermore, their exposure to winter heatwaves resulted in 75% to 100% mortality. Feeding on the native host provided higher resilience under thermal stress than feeding on the invasive, recently acquired host. Finally, both heatwave incidence and severity have increased in the southern range of E. p. phaeton in the period from 1894 to 2011. We show that warm winter days induced severe mortality, providing a mechanistic explanation of how climate change can trigger population declines in E. p. phaeton and other insects.